Students' Perception of Using Speak PAl in Learning Speaking At Sma Negeri 1 Panyabungan Selatan - Khairani , Nikmah; Fitriani , Fitriani; Lubis , Rica Umrina (MUDABBIR Journal Research and Education Studies, 2025)
The study employed a qualitative research design with interviews as the primary instrument of data collection. The participants of this research were eleventh-grade students who had experience in using the application. The focus of the study was on three main aspects: the ways in which students use the SpeakPal application in their learning process, their perceptions of the advantages and usefulness of this tool to increase speaking ability, and the challenges they encounter during its implementation.The findings revealed that most students expressed positive perceptions toward the application. They viewed Speak Pal as a practical, enjoyable, and helpful tool that provides opportunities to practice speaking at any time and in any place, beyond classroom limitations. The features offered, such as daily speaking exercises, pronunciation practice, and interactive conversations, were considered effective in building students’ confidence, enriching vocabulary, and supporting independent learning. In addition, SpeakPal was reported to reduce feelings of shyness and nervousness, thus increasing students’ fluency when speaking English. Nevertheless, some obstacles were identified, including unstable internet connectivity, restricted access to premium features, and occasional difficulty in understanding automated feedback provided by the application.In conclusion, the study emphasizes that SpeakPal significantly contributes to students’ speaking development. The findings further suggest that integrating applications like Speak Pal into English learning can enhance motivation, foster learner autonomy, and improve students’ overall speaking proficiency.